Book Review. Elisha McIntyre, Religious Humor in Evangelical Christian and Mormon Culture Journal for Religion, Film and Media - Marie-Therese Mäder (Journal for Religion, Film and Media, 2020)
At first sight one might think that religion and humor contradict each other or at least are not a fruitful pair. The study Religious Humor in Evangelical Christian and Mormon Culture by Elisha McIntyre, an Australian scholar in the study of religion, shows that this isn't true at all, although differences in the effectiveness of humor persist depending on its purpose and the involved agents.